2018
DOI: 10.1038/s41467-017-02705-8
|View full text |Cite
|
Sign up to set email alerts
|

DNA multi-bit non-volatile memory and bit-shifting operations using addressable electrode arrays and electric field-induced hybridization

Abstract: DNA has been employed to either store digital information or to perform parallel molecular computing. Relatively unexplored is the ability to combine DNA-based memory and logical operations in a single platform. Here, we show a DNA tri-level cell non-volatile memory system capable of parallel random-access writing of memory and bit shifting operations. A microchip with an array of individually addressable electrodes was employed to enable random access of the memory cells using electric fields. Three segments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 40 publications
0
28
0
Order By: Relevance
“…Latencies of hard-drives and low read-write cycle times will be difficult to achieve. However, advances in DNA-based non-volatile memory combined with logical operations 22 and innovative synthesis methods using e.g., UV patterning and DNA self-assembly 23 help to alleviate this gap. It can be anticipated that improving the number of oligos synthesized in parallel and further optimizations reagent usage will get synthesis costs down to the 1 US$ MB −1 region rapidly.…”
Section: Discussionmentioning
confidence: 99%
“…Latencies of hard-drives and low read-write cycle times will be difficult to achieve. However, advances in DNA-based non-volatile memory combined with logical operations 22 and innovative synthesis methods using e.g., UV patterning and DNA self-assembly 23 help to alleviate this gap. It can be anticipated that improving the number of oligos synthesized in parallel and further optimizations reagent usage will get synthesis costs down to the 1 US$ MB −1 region rapidly.…”
Section: Discussionmentioning
confidence: 99%
“…By taking advantage of DNA modification techniques with microfluidic platforms, Nguyen et al [25k] developed an onchip fluorescence switching (ON" and "OFF") system (Figure 6E) based on DNA strand displacement (with an intercalating dye, Sybr Green I) and DNA hybridization (signal at "ON" = "1" and signal at "OFF" = "0") for a rewritable and random access data storage device. Song et al [72] developed a DNA tri-level cell non-volatile memory system capable of parallel random-access writing of memory and reading eight combinations of three-bit data by electricfield-induced strand displacement (shifting operations) of fluorescently labeled complementary probes imaging technique. This switching operation opens new possibilities for DNA computation, which would be necessary for truly rapid, digital-like programming and responses.…”
Section: Dna Modificationmentioning
confidence: 99%
“…Recently, combining with DNA strand replacement, Song et al [ 100 ] demonstrated the rapid parallel writing and reading of 2 3 combinations of 3‐bit memory data and bit shifting operations by electric field‐induced strand displacement. DNA photolithography enables storage of pattern information.…”
Section: In Vitro Data Storage Based On Dna Nanoengineeringmentioning
confidence: 99%